2009
DOI: 10.1038/sj.bjc.6605096
|View full text |Cite
|
Sign up to set email alerts
|

The association between the T309G polymorphism of the MDM2 gene and sensitivity to anticancer drug is dependent on the p53 mutational status in cellular models

Abstract: BACKGROUND: We investigated, in the panel of 60 human tumour cell lines of the National Cancer Institute (NCI-60), whether the R72P polymorphism of TP53 and the T309G polymorphism of MDM2 were associated to the in vitro cytotoxicity of anticancer agents, extracted from the NCI database. For validation, the same study was performed independently on a second panel of tumour cell lines, JFCR-45. METHODS: Both SNPs were identified in cell DNA using PCR-RFLP techniques confirmed by direct sequencing and by pyrosequ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
3
0

Year Published

2011
2011
2018
2018

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(5 citation statements)
references
References 31 publications
2
3
0
Order By: Relevance
“…We observed a higher frequency of MDM2, but not MDM2-C, tumors in Japanese patients, compared to White and Native Hawaiian patients (Table 2). Interestingly, several studies have found interactions between the MDM2 SNP309 genotype and p53-pathway status and breast cancer survival [44][45][46]. Similar interactions may contribute to the association differences that we are observing for the different racial/ethnic groups in our study.…”
Section: Discussionsupporting
confidence: 78%
“…We observed a higher frequency of MDM2, but not MDM2-C, tumors in Japanese patients, compared to White and Native Hawaiian patients (Table 2). Interestingly, several studies have found interactions between the MDM2 SNP309 genotype and p53-pathway status and breast cancer survival [44][45][46]. Similar interactions may contribute to the association differences that we are observing for the different racial/ethnic groups in our study.…”
Section: Discussionsupporting
confidence: 78%
“…Although a single 1992 report noted a point mutation of p53 in codon 158 of exon 5 in H226 cells (15), we and several other investigators have confirmed the wt status of p53 without a point mutation in codon 158 in the H226 line ( Supplementary Fig. S2) (16-18). We therefore transiently transfected a full length wt p53 into the Cet-R cells using a pC53-SN plasmid.…”
Section: Resultssupporting
confidence: 56%
“…In addition, an earlier age at onset of tumors was seen in Li-Fraumeni patients carrying the rare MDM2 GG-genotype compared to the T-allele carriers [23,29]. Another study performed in human tumor cell lines showed that the MDM2 SNP309 gene polymorphism had a major impact on the sensitivity to DNA-interfering drugs, especially in TP53 non-mutated cell lines [30]. These data together seem to suggest, though to some extent in opposite directions, that additional genetic changes in the tumor might be required for MDM2 SNP309 to induce and/or accelerate tumor progression.…”
Section: Introductionmentioning
confidence: 94%